Enhancement of the bioactive compound content in strawberry fruits grown under iron and phosphorus deficiency. (16th October 2014) - Valentinuzzi, Fabio; Mason, Marco; Scampicchio, Matteo; Andreotti, Carlo; Cesco, Stefano; Mimmo, Tanja
Abstract BACKGROUND Among berries, strawberry fruits are one of the richest natural sources of health‐beneficial components such as micronutrients, antioxidants and phytochemicals. Strawberry quality depends greatly upon genotype, environmental factors, cultivation techniques and nutrient supply. This study aimed to assess the influence of phosphorus and iron deficiency on the bioactive compound content in strawberry fruits grown under hydroponic conditions. RESULTS Different nutrient supplies clearly influenced the qualitative parameters of strawberry fruits. Principal component analysis (PCA) showed that three homogeneous clusters could be identified. The three treatments (control, iron deficiency and phosphorus deficiency) differed especially because of their phenolic compounds and antioxidant potential, the strawberry fruits grown under Fe and P deficiency being richer in pelargonidin‐3‐glucoside, benzoic acids and flavonols than the control fruits. CONCLUSION Nutrient deficiency had a positive effect on nutritional parameters of strawberry fruits without impairing fruit yield and quality parameters such as acidity, firmness and total soluble solid content. The shaping of nutrient availability in the growing medium could thus be of help in producing an edible yield with the desired qualitative aspects and nutritional value. © 2014 Society of Chemical Industry